2018
DOI: 10.1002/jwmg.21507
|View full text |Cite
|
Sign up to set email alerts
|

Integrated modeling to estimate population size and composition of mule deer

Abstract: Estimating population size, age composition, and sex ratio of mule deer (Odocoileus hemionus) is important to conservation and managed hunting of this species in the western United States. Increasingly, wildlife agencies are estimating abundance of deer using fecal DNA (fDNA), especially in forested habitats where aerial surveys are not feasible. These same data can be used to estimate overall sex ratio but require additional data on age structure to quantify adult‐ and fawn‐specific sex ratios, which are expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 49 publications
5
56
2
Order By: Relevance
“…Our density estimates of approximately 8 deer/km 2 are higher than those from a study approximately 300 km to the north of our study site which found approximately 5.0 (95% CI = 2.3-7.8) deer/km 2 ; however, the 95% confidence and credible intervals overlap (Brazeal et al 2017). Our density estimates and credible intervals are higher than the estimate of 5.2 deer/km 2 (90% CRI = 4.4-6.1) reported by Furnas et al (2018) in a study approximately 450 km to the north of our study site. The lower density estimates reported in these studies may be due to the more mountainous and heavily forested terrain that may not provide the same forage resources and support the same densities of deer as the milder coastal environment where we conducted this study.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Our density estimates of approximately 8 deer/km 2 are higher than those from a study approximately 300 km to the north of our study site which found approximately 5.0 (95% CI = 2.3-7.8) deer/km 2 ; however, the 95% confidence and credible intervals overlap (Brazeal et al 2017). Our density estimates and credible intervals are higher than the estimate of 5.2 deer/km 2 (90% CRI = 4.4-6.1) reported by Furnas et al (2018) in a study approximately 450 km to the north of our study site. The lower density estimates reported in these studies may be due to the more mountainous and heavily forested terrain that may not provide the same forage resources and support the same densities of deer as the milder coastal environment where we conducted this study.…”
Section: Discussioncontrasting
confidence: 86%
“…The n jk records of unmarked deer are assigned to M hypothetical individuals, where M is chosen larger than the expected population size to not truncate the estimate of the number of unmarked individuals in the population. We used a value of 450 because this population density was more than twice that reported in other recent studies in California (Furnas et al 2018). The model then estimates a latent individual covariate (z i ), which is 1 if the animal is part of the population, and 0 otherwise, using a Bernoulli distribution,…”
Section: Ijk Ijk Jkmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the quantitative increase in numbers of loci available translates to a qualitative shift in how best to address the misclassification problem. Rather than assessing the minimum number of loci to minimize one of these errors (falsely lumping 2 individuals) under very stringent conditions of zero genotyping error (e.g., Taberlet et al , Waits and Leberg , McKelvey and Schwartz ), use of sufficiently large numbers of loci can be used to simultaneously minimize both types of misclassification errors, while explicitly incorporating a known and acceptable level of genotyping error (e.g., 2–3%; Lounsberry et al , Furnas et al ). The present study utilized 3 multiplex reactions, averaging approximately 6 markers each (including the sex marker), such that genotyping in duplicate required only 12 μL of extracted DNA and 6 total reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, estimation of abundance (i.e., census population size, N c ) should be based on a systematic survey design, which enables application of standard spatially agnostic capture–recapture estimators (e.g., Miller et al , Lounsberry et al ) and more powerful spatial mark–recapture methods (e.g., Brazeal et al , Furnas et al , Lonsinger et al ). Our present study was based on a relatively small sample size; therefore, we used a simple approach found to be especially useful for small populations of rare, wide‐ranging carnivores, based directly on the distribution of recaptures, as implemented in Program Capwire (Miller et al ).…”
Section: Methodsmentioning
confidence: 99%